Occurrence of vanA/vanM-positive vancomycin-resistant Enterococcus faecium in hospital wastewater associated with clinical infections in Guangzhou, China: A genomic epidemiological study - Liling Zhang; Minxuan Su; Shaowei Meng; Xuan Zhang; Hao Wu; Meina Wu; Xiaojun Ao; Xiaoyue Zhang; Jiehao Lin; Shijia Yu; Yuqi Hong; Xiucheng Zeng; et al. (International Journal of Medical Microbiology)
Background: The emerging ST80 vancomycin-resistant Enterococcus faecium (VREfm) lineage, linked to the increases of clinical infections in China and Japan, raises concerns about environmental transmission. Hospital wastewater systems are recognized reservoirs for antimicrobial-resistant bacteria, but their role in disseminating ST80 VREfm remains unclear. This study investigates VREfm prevalence in hospital wastewater and genomic links between patients and hospital wastewater. Methods: From December 2023 to May 2024, a total of 262 wastewater samples were collected from three hospitals in Guangzhou, China. VREfm was identified using vancomycin-supplemented media. Antimicrobial susceptibility was assessed using the broth dilution method. Ninety-five patient-derived VREfm genomes in the same hospitals were included. Whole-genome sequencing and bioinformatic analysis were performed to reveal genomic characterizations and genetic transmission links. Results: VREfm was detected in 54.6 % (143/262) of samples. All isolates carried vanA, with 25.9 % (37/143) co-harboring vanA and vanM. The dominant ST80 lineage (43.4 %, n = 62) was linked to recent regional prevalence. A novel sequence type ST2460, belonging to CC17, emerged as the second most prevalent (27.2 %, n = 39). ST80 isolates exhibited enriched antimicrobial resistance genes, correlating with multidrug resistance phenotypes and high resistance rates. Genomic analysis revealed that 95.7 % (132/138) of ST80 isolates from wastewater and patients exhibited close genetic relatedness (median of SNP = 19, IQR: 14–23) and were linked within cross-source transmission networks, supported by the high similarity of a shared p23VRE019-like plasmid. Conclusions: Hospital wastewater is a critical reservoir for high-risk VREfm clones, particularly the outbreak-associated ST80 lineage. The persistence of VREfm in effluents and evidence of cross-source transmission underscores the urgent need for enhanced environmental surveillance. Integrated strategies addressing environmental reservoirs are essential to combat the growing threat of VREfm.